2013
DOI: 10.1002/ejic.201300548
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II) Complexes of N,N‐Diisopropylpicolinamide – Solvatochromic and Thermochromic Phase Change of a Monomeric Complex to a Ferromagnetically Coupled Dimeric Complex

Abstract: The synthesis and characterization of mononuclear [Cu(L) 2 -(Cl) 2 ] (1), dinuclear [{CuCl(L)} 2 (μ-Cl) 2 ] (2), and another mononuclear complex [Cu(L) 2 (ClO 4 ) 2 ] (3) with a bidentate N,Ndiisopropylpicolinamide ligand (abbreviated L) are described. Complexes 1 and 2 were obtained from the same reaction mixture and show thermo-and solvatochromic behavior. Complex 1 shows irreversible thermochromism by changing into 2 upon heating at 160°C. These two complexes also show solvatochromism in various solvents. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…A similar trend has been found in other copper complexes [74]. As a consequence of the weak Cu-Cl (bridging) bonds such packing arrangement in complex 1 is not sustained in solution where the solvent has strong donor atoms [75]. Complex 1 and complex 2 both have identical 8-aminoquinoline rings as part of the tridentate ligand.…”
Section: Crystal Structuresupporting
confidence: 65%
“…A similar trend has been found in other copper complexes [74]. As a consequence of the weak Cu-Cl (bridging) bonds such packing arrangement in complex 1 is not sustained in solution where the solvent has strong donor atoms [75]. Complex 1 and complex 2 both have identical 8-aminoquinoline rings as part of the tridentate ligand.…”
Section: Crystal Structuresupporting
confidence: 65%
“…The band in the range of 630-520 cm −1 corresponds to the M-Cl bond. [34] All edifices are likewise shown groups because of facilitated water particles. The groups in the range 747-854 and 614-623 cm −1 showed up in the spectra of these buildings, which might be allotted to δr(H 2 O) and δw(H 2 O), individually.…”
Section: Ir Spectramentioning
confidence: 97%
“…There are several copper(II) dimeric compounds in which the copper atoms are bridged by chlorido ligands (Marsh et al, 1983;Puschmann et al, 2001;Li et al, 2006;Lee, et al, 2008;Han et al, 2008;Øien et al, 2013;Choubey et al, 2015;Golchoubian & Nateghi 2016;Liu et al, 2009). A search of the Cambridge Structural Database (Version 5.38, November 2016; Groom et al, 2016), revealed numerous di--chlorido bridged copper(II) compounds constructed with ligands having -N,O-donor atoms (Kapoor et al, 2002(Kapoor et al, , 2004Damous et al, 2013;Lumb et al, 2013;Smolentsev et al, 2014;Qureshi et al, 2016). However, the search did not reveal related complexes derived from pyridine-2,4-dicarboxylic acid and piperazine.…”
Section: Database Surveymentioning
confidence: 99%